PENGARUH DOSIS KOMPOS AZOLLA DAN KALIUM ORGANIK TERHADAP KETERSEDIAAN KALIUM DAN HASIL KACANG TANAH PADA ALFISOL - Lutfy Ismoyo; Sumarno Sumarno; Sudadi Sudadi (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2013)
Title : The Effect of Azolla Compost and Organic Pottasium Fertilizer Dosages on Pottasium Availability and Yield of Peanut on Alfisol. Production of groundnut can not meet the national demand right now. One of the reason is the degradation in soil fertility, such as potassium deficiency and low of soil organic matter content. Plants that has potassium-deficiency can not utilize water and nutrients from the soil efficiently. In organic farming system, soil exchangeable-potassium and organic matter content can be increase by the application of plant ash as organic potassium and azolla compost. The research conducted to determine the proper dose of azolla compost and organic potassium to increase exchangeable-potassium and yield of groundnut on Alfisol soil at Jumantono, Karanganyar District, Central Java, Indonesia. The experiment was arranged in Completely Randomized Design (CRD) with single treatment factor of azolla compost and organic pottasium combination (P1, P2, P3, P4, P5, P6, P7, P8) as well as manure and NPK fertilizer treatments. The Variables using in this experiment are K exchanged, CEC, Organic Matter, Total N, pH, plant height, fresh weight and dry stover, fresh weight, dry and number of pods, weight and number of seeds. Data were analyzed by F test and DMRT at 5% level. The land use media as much as 5 kg per polybag with 3 number plants per poybag, and in the second week we used to thinning the plants. Everyday we also doing watering and weeding. The observation were made every week until phase of generatif The results showed the application of azolla compost and organic potassium can increase exchangeable-potassium and yield of groundnut in Alfisol soil. The highest exchangeable-pottasium (0.53me%) taken from the treatment of P7. Moreover the application of azolla compost and organic potassium increased CEC, soil organic matter content, total-N soil as well as shoot fresh and dry weight of peanut.